Um estudo exploratório de uma linguagem inclusiva nos meios audiovisuais no contexto sociopolítico de Hong Kong - Gabriela da Costa Ferreira (2020)
The dissemination of information and the right to education are, undoubtedly, elements to which each individual must have access, regardless of their social status, ethnicity or culture. Political documentary plays a fundamental role, with immeasurable power, when it comes to sharing information through audiovisual media and must be able to respect the needs of each individual who attends it. With this idea in mind, and inserted in the current socio-political context of Hong Kong, it is put into practice the making of a documentary combined with an ideology and political exposure, for later production of solutions that aim to respect and include viewers with visual and hearing impairments. My goal is that with the obtained results and with the methodology that will be developed, a step forward will be possible in the creation of an inclusive language in audiovisual media, as well as the articulation of three roles assumed as a researcher, artist and activist.